Food solidarities for and with migrants: mobilizations under pressure in public spaces in the Bordeaux area. - Crenn, Chantal; Marchiset, Sarah; Téchoueyres, Isabelle (Food, Culture & Society, 2025)
This article explores the social processes of solidarities under pressure and their articulation with food in migratory contexts, in both urban and rural settings around Bordeaux (Gironde, South-West France). It is based on the actual experiences of vulnerable individuals in migration situations (the Outsiders) and "the Established" (cf. Elias and Scotson), who engage in various actions for, and sometimes with, the former. Our methodology included observing participants in several dwelling places and food-aid initiatives, as well as conversations with adults, unaccompanied minors, and families. Adopting an "embedded" anthropology approach (Dubey; Lewis and Russell), we followed long-term residents and new arrivals in their interactions. We conducted a multi-level analysis of the different approaches and positions adopted by the protagonists providing and receiving assistance, sometimes both at once, exerting their agency in order to create spaces of freedom within structural constraints, thus expressing their participation in society. One of the aims was to contribute to a situational anthropology approach that ultimately challenged the position of foreigners in our societies.